Natural Polymer Drug Delivery Systems Nanoparticles, Plants, and Algae - Bhatia, Saurabh; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book describes 200 bio-polymers, including the most recent and advanced nanotechnology applications. The applications of various bio-medical and other future potential uses are covered and examined in depth. Systematic discussion of current leading natural polymers is also included.
Ch.1. Nanotechnology and Its Drug Delivery Applications -- Ch.2. Nanoparticles Types, Classification, Characterization, Fabrication Methods and Drug Delivery Applications -- Ch.3 Natural Polymers Vs Synthetic Polymer -- Ch.4 Plant Derived Polymers, Properties, Modification & Applications -- Ch.5 Marine Polysaccharides Based Nano-materials and Its Applications.
Keywords: Polymers; Nanotechnology; Biomedical engineering; Pharmaceutical chemistry; Polymers; Nanotechnology; Biomedical Engineering and Bioengineering; Pharmaceutics